Segmentasi Penerapan Harga Produk Kacamata Berdasarkan Segmentasi Pasar di Optik YAR Padang - Fadjar Adhiyaksa; Jihan Atifa; Yuliana Fransiska; Vivi Nila Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
Effective pricing is a key factor in enhancing competitiveness and customer satisfaction in the optical industry. This study aims to analyze the pricing strategy of eyeglass products based on market segmentation at Optik YAR Padang. Market segmentation was conducted by grouping consumers according to demographic, psychographic, and purchasing behavior characteristics. The research employed a quantitative approach using survey questionnaires distributed to customers, and the data were analyzed using cross-tabulation and chi-square tests. The results show significant differences in price preferences among various market segments, particularly based on age, income level, and the purpose of eyeglass use (fashion or vision correction). The findings recommend that Optik YAR implement differentiated pricing strategies tailored to each target segment, such as economic pricing for students and premium pricing for professionals. By applying segmentation-based pricing strategies, the company can improve customer loyalty and sales efficiency.